PHYSIO-ANATOMICAL EVALUATION OF SOME TREE SPECIES FOR AFFORESTATION IN DRY REGION OF KOGI STATE, NIGERIA - Omolokun, K. T.; Oluwa, O. K.; Sharaibi, O. J.; Adu, A. A.; Osinaike, T. S.; Ojewumi, A. W.; Keshinro, O. M.; Oyetunji, O. S.; Ogbe, A. A.; Mamudu, M. M. (FUDMA Journal of Sciences, 2024)
The stomatal features of plant species have ability to release water vapour into the air. Hence, correlations between the stomatal features and transpiration rate of five tree species namely Danielli oliveri, Delonix regia, Piliostigma thonningii, Azadirachta indica and Tectona grandis was studied to evaluate their capacity for afforestation. The leaf epidermal layers were isolated using nail polish; they were observed under the light microscope to examine their stomatal features. The transpiratiom rate was evaluated using the cobalt chloride method. The results revealed that Delonix regia and Piliostigma thonningii are amphistomatic; while the remaining three species are hypostomatic. The stomatal complex types observed are anomocytic, brachyparacytic and paracytic, The stomatal density ranged from 14.41 mm-2 to 93.61 mm-2; the stomatal index ranged from 7.15% to 28.23%; while the stomatal size ranged from 11.19 µm2 to 29.36 µm2. The study revealed that stomatal traits such as hypostomatic leaf nature, stomatal complex types (i.e. paracytic, brachyparacytic), low stomatal index, small stomatal size possessed by the plant species may be responsible for their lower rate of transpiration; which in turn might be suitable for their afforestation in dry areas. Therefore, Tectona grandis which released the lowest amount of water (2.49 × 10-6 mol m-2s-1) into the atmosphere might be the most suitable for afforestation, followed by Piliostigma thonningii, Daniellia oliveri, Delonix regia and lastly Azadirachta indica (2.97 × 10-6 mol. m-2s-1). Conclusively, the stomatal features showed positive correlations with transpiration rates; thereby enhancing the potentials of the studied species for afforestation in dry region.